Desentralisasi dan Otonomi Daerah; Pelaksanaan Otonomi Khusus Papua Berdasarkan Sistem UUD Negara Republik Indonesia Tahun 1945 - Ibrahim Ibrahim; Juanda Juanda (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Indonesia as a nation-state accommodates a lot of cultural diversity that grows in society. The 1945 Constitution of the Republic of Indonesia has mandated a form of the regional government, which regulates and manages government affairs on its own according to the principles of autonomy and co-administration. This is directed at accelerating the realization of community welfare through improvement, service, empowerment, and community participation, as well as increasing regional competitiveness by taking into account the principles of democracy, equity, justice, privilege and specificity of a region in the system of the Unitary State of the Republic of Indonesia. The provisions in the constitution mandate the Unitary State of the Republic of Indonesia to be carried out with inter-regional arrangements that are not uniform between one another. In the relationship between the centre and the regions or the province and districts/cities, it is possible to have a special relationship pattern, such as the Papua province. Such arrangements are intended to ensure that the entire Indonesian nation is truly united with diversity within the framework of the Unitary State.Keywords: Regional Autonomy; Implementation of Papua's Special Autonomy; 1945 Constitution AbstrakIndonesia sebagai Negara Bangsa (nation state) mewadahi banyak keragaman budaya yang tumbuh di dalam masyarakat. Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, telah mengamanatkan suatu bentuk pemerintahan daerah, yang mengatur dan mengurus sendiri urusan pemerintahan menurut asas otonomi dan tugas pembantuan. Hal ini diarahkan untuk mempercepat terwujudnya kesejahteraan masyarakat melalui peningkatan, pelayanan, pemberdayaan, dan peran serta masyarakat, serta peningkatan daya saing daerah dengan memperhatikan prinsip demokrasi, pemerataan, keadilan, keistimewaan dan kekhususan suatu daerah dalam sistem Negara Kesatuan Republik Indonesia. Ketentuan-ketentuan dalam konstitusi tersebut, mengamanatkan Negara Kesatuan Republik Indonesia diselenggarakan dengan pengaturan antar daerah yang tidak seragam antara satu sama lain. Dalam hubungan antara pusat dan daerah atau daerah propinsi dengan kabupaten/kota dimungkinkan adanya pola hubungan yang bersifat khusus seperti propinsi Papua. Pengaturan demikian dimaksud untuk menjamin agar seluruh bangsa Indonesia benar-benar bersatu dengan keragaman dalam bingkai Negara Kesatuan.Kata Kunci: Otonomi Daearah; Pelaksanaan Otonomi Khusus Papua; UUD Negara 1945